Role of Nb in the failure of dual-phase steel in heterogeneous welds. (October 2020) - Schmidová, Eva; Sunil Kumar, M.R.; Schmid, Michal; Bozkurt, Fatih
Highlights: Nb-based intermetallics lead to hot cracking in two-phase stainless steel. Delta ferrite affects the Nb-based intermetallics in two-phase steel. Carbon redistribution can suppress sensitivity to hot cracking. Abstract: The use of Cr-Ni austenitic steel interlayers is an effective solution for heterogeneous welds, especially in combination with high-carbon steels. High contact-fatigue resistance and resistance to impact loads are required in the case of railway crossing applications. The failure of Nb-alloyed cast Cr-Ni austenitic steel used as an insert in the flash butt resistance weld of Hadfield steel with carbon steel is the subject of the presented analyses. The identification of the failure mechanism is based on light and scanning electron microscopy and energy dispersive X-ray analyses, including electron backscattered analyses. The initiation of hot-crack defects is detected in the heat affected zone (HAZ). In contrast to the usual conditions for the formation of hot cracks in the HAZ, cracks are found solely outside the superheating zone. The decisive influence of Nb-based intermetallics formed at the phase interface of δ-ferrite and the austenitic matrix is indicated. The eutectics formation between niobium carbonitrides and the austenitic matrix is assumed to be responsible for the hot-cracking susceptibility of austenitic steel. The particular combination of the temperature gradient together with the chemical gradient leading to a localization of the critical zone is documented. The paper describes the influence of carbon redistribution at the weld interface on the morphology of delta-ferrite in different layers of the heat-affected zone. Induced structural differences are associated with Nb-particle formation. Fractographic analyses show the formation of low-melting phases in the critical layer of the HAZ. The influence of secondary phases, especially Nb-eutectic, on the degradation of austenitic steel plasticity is documented.